Preliminary considerations for electronic medical record (EMR) in the public hospitals of Gandaki province in Nepal - Gauchan, Bikash; Sherchan, Rekha; Tiwari, Shreeram; Khadka, Khim B (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Electronic Medical Record (EMR) is the digital tool to keep records of valuable information on computer or computer-like equipment, regarding health systems, including patient’s records and stock management which can provide real time evidence for better patient record, clinical care and health policy making. As Nepal does not have a national EMR system, and it is a challenge to get real time data, information and evidence required for effective health policy making. With an effective national EMR system in Nepal, the health system can be improved with reliable information of patients for the continuity of clinical care. There are existing scientific evidence of EMR on the lessons of implementation in Nepal, opportunities for the use of EMR in Malaysia, perspectives of health care workers on EMR after its implementation in Canada, on the development of success measuring tools and the use of questionnaires for the EMR implementation in Canada, best practices, impact of EMR on physician practice, and barriers for EMR implementation. EMR can improve the quality, effectiveness, transparency and efficiency of healthcare services and its management. Gandaki province is one of seven provinces in Nepal and is exploring ways to implement EMR in all the hospitals operated under the province government. There can be step wise approach to have EMR in all of these hospitals. This can give more strategies for the national EMR system.